Pidge, Texas Ranger - Parsons, Chuck (Texas A & M University Press, 2013)
Thomas C. (Pidge) Robinson came to Texas from Virginia at the age of 27, fleeing a feud with a neighbor who opposed Robinson's amorous intentions toward the neighbor's sister. He joined the Texas Rangers in 1874, serving with legendary Capt. Leander H. McNelly's Washington County Volunteer Militia Company A. He earned the rank of first lieutenant in this Texas Ranger company. Two years later he returned to Virginia to avenge his honor and claim the woman he loved. A learned and witty writer who sent back letters, poems, and reports for publication in Aus.